Skulpturenweg Nordhorn - Landkreis Grafschaft Bentheim Stadt Nordhorn 1977-1994. - Brüggemann, Josef; Dylla, Sabine; Krebs, Harald (Nordhorn : Städtische Galerie Nordhorn, 1994)
Nils-Udo ; Luginbühl, Bernhard ; Deacon, Richard ; Dodeigne, Eugène ; Schad, Robert ; Hauser, Erich ; Bühl, Hede ; Visch, Henk ; Holzer, Jenny ; Ulrichs, Timm ; de Locht, Peter van ; Möbus, Christiane ; Baumann, Herbert ; Buxel, Reinhard ; Fujiwara, Hokoto ; Rogge, Cornelius ; Damsté, Christiaan Paul ; Schoenholtz, Michael ; Prantl, Karl ; Damsté, Christiaan Paul ; Pabel, Rudi ; Kubach-Wilmsen-Team ; Glossner, Wolf ; Rübsam, Peter ; Rückriem, Ulrich ; Niebuhr, Louis
Duits
boek
Keywords: Nordhorn